Characterisation and Modelling of Manufacturing–Microstructure–Property–Mechanism Relationship for Advanced and Emerging Materials - Su, Lihong; Wei, Peitang; Zhao, Xing; Wang, Hui (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint is a collection of papers published in a Special Issue that collected the recent advances within and investigations of the research fields of manufacturing and the characterisations or modelling of materials. The variety and quality of all these papers are addressed to both academic and industrial researchers who are looking for new information that can contribute to the advancement of future research in these highly challenging fields.